Chronic social stress in mice alters energy status including higher glucose need but lower brain utilization. (September 2020) - Carneiro-Nascimento, Simone; Opacka-Juffry, Jolanta; Costabile, Adele; Boyle, Christina N.; Herde, Adrienne Müller; Ametamey, Simon M.; Sigrist, Hannes; Pryce, Christopher R.; Patterson, Michael
Highlights: Chronic social stress (CSS) leads to increased energy need. CSS leads to increased dependence on carbohydrate as energy source. CSS leads to reduced insulin and slower glucose clearance. CSS leads to increased ghrelin and reduced leptin. CSS leads to lower glucose utilization by the brain. Abstract: Chronic stress leads to changes in energy status and is a major risk factor for depression, with common symptoms of reductions in body weight and effortful motivation for reward. Indeed, stress-induced disturbed energy status could be a major aetio-pathogenic factor for depression. Improved understanding of these putative inter-relationships requires animal model studies of effects of stress on both peripheral and central energy-status measures and determinants. Here we conducted a study in mice fed on a standard low-fat diet and exposed to either 15-day chronic social stress (CSS) or control handling (CON). Relative to CON mice, CSS mice had attenuated body weight maintenance/gain despite consuming the same amount of food and expending the same amount of energy at any given body weight. The low weight of CSS mice was associated with less white and brown adipose tissues, and with a high respiratory exchange ratio consistent with increased dependence on glucose as energy substrate. Basal plasma insulin was low in CSS mice and exogenous glucose challenge resulted in a relatively prolonged elevation of blood glucose. With regard to hunger and satiety hormones, respectively, CSS mice had higher levels of acylated ghrelin in plasma and of ghrelin receptor gene expression in ventromedial hypothalamus and lower levels of plasma leptin, relative to CON mice. However, whilst CSS mice displayed this constellation of peripheral changes consistent with increases in energy need and glucose utilization relative to CON mice, they also displayed attenuated uptake of [ 18 F]FDG in brain tissue specifically. Reduced brain glucose utilization in CSS mice could contribute to the reduced effortful motivation for reward in the form of sweet-tasting food that we have reported previously for CSS mice. It will now be important to utilize this model to further understanding of the mechanisms via which chronic stress can increase energy need but decrease brain glucose utilization and how this relates to regional and cellular changes in neural circuits for reward processing relevant to depression.